1980
DOI: 10.1128/jcm.11.1.52-58.1980
|View full text |Cite
|
Sign up to set email alerts
|

Rapid differentiation of the major causative agents of bacterial meningitis by use of frequency-pulsed electron capture gas-liquid chromatography: analysis of amines

Abstract: The major causative agents of bacterial meningitis (Haemophilus influenzae serogroup B, Neisseria meningitidis serogroups B and C, Klebsiella pneumoniae, Steptococcus pneumoniae, and two types of Escherichia coli) were cultured in a chemically defined medium, and selected strains were further studied in Todd-Hewitt medium. After acidic extraction of the spent media with chloroform, a basic extraction was made with chloroform to obtain amines. A third extraction was performed on re-acidified Todd-Hewitt medium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
0

Year Published

1981
1981
1987
1987

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 11 publications
0
21
0
Order By: Relevance
“…For carboxylic acids, the acidic chloroform extract was derivatized with trichloroethanol (TCE) as previously described (1). The samples were also analyzed for amines and hydroxy acids as previously described (2,(6)(7)(8).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For carboxylic acids, the acidic chloroform extract was derivatized with trichloroethanol (TCE) as previously described (1). The samples were also analyzed for amines and hydroxy acids as previously described (2,(6)(7)(8).…”
Section: Methodsmentioning
confidence: 99%
“…The bromination procedure was done as follows. (i) The TCE-derivatized sample in xylene-ethanol (50:50) was evaporated with clean, dry air (1,7) to about 25 ,ul, and 100 pul of a 50:50 CHCl3-CCL4 solution was added. (ii) A 25-pul portion of a solution of 5% bromine in CCl4 was added, and the reaction mixture was permitted to sit for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…Next, the residual basic aqueous phase was acidified to about pH 2 with H2SO4 and extracted with 20 ml of ethyl ether (Fisher reagent grade stabilized with butylated hydroxytoluene) to obtain hydroxy acids. The acidic chloroform extracts were derivatized with trichloroethanol-heptafluorobutyric anhydride (TCE-HFBA) to form TCE esters of carboxylic acids and HFBA esters of alcohols as described (1,6). The basic chloroform extracts containing amines and the acidic ethyl ether extracts containing hydi-oxy acids were derivatized with HFBA pyridine-ethanol to form amides and esters, respectively, as described (2, 7).…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have shown that frequencypulsed electron capture gas-liquid chromatography (FPEC-GLC) of body fluids (pleural fluids and cerebrospinal fluids) is a promising tech-nique for classifying various types of pleural effusions (3) and for distinguishing among tuberculous, cryptococcal, and viral meningitis (5,8). FPEC-GLC has also been used in spent-media analysis to distinguish organisms at the species and strain levels (6,7).…”
mentioning
confidence: 99%
See 1 more Smart Citation